Correlation between stoichiometry and surface structure of the polar MgAl2O4(100) surface as a function of annealing temperature. Issue 8 (28th January 2015) - Jensen, Thomas N.; Rasmussen, Morten K.; Knudsen, Jan; Vlad, Alina; Volkov, Sergey; Lundgren, Edvin; Stierle, Andreas; Lauritsen, Jeppe V.
Abstract : Experimental characterization of the polar MgAl2 O4 (100) surface revealing a strong correlation between annealing temperature and surface morphology. Abstract : The correlation between surface structure, stoichiometry and atomic occupancy of the polar MgAl2 O4 (100) surface has been studied with an interplay of noncontact atomic force microscopy, X-ray photoelectron spectroscopy and surface X-ray diffraction under ultrahigh vacuum conditions. The Al/Mg ratio is found to significantly increase as the surface is sputtered and annealed in oxygen at intermediate temperatures ranging from 1073–1273 K. The Al excess is explained by the observed surface structure, where the formation of nanometer-sized pits and elongated patches with Al terminated step edges contribute to stabilizing the structure by compensating surface polarity. Surface X-ray diffraction reveals a reduced occupancy in the top two surface layers for both Mg, Al, and O and, moreover, vacancies are preferably located in octahedral sites, indicating that Al and Mg ions interchange sites. The excess of Al and high concentration of octahedral vacancies, very interestingly, indicates that the top few surface layers of the MgAl2 O4 (100) adopts a surface structure similar to that of a spinel-like transition Al2 O3 film. However, after annealing at a high temperature of 1473 K, the Al/Mg ratio restores to its initial value, the occupancy of all elements increases, and the surface transforms into a well-defined structure with large flat terraces and straight step edges, indicating a restoration of the surface stoichiometry. It is proposed that the tetrahedral vacancies at these high temperatures are filled by Mg from the bulk, due to the increased mobility at high annealing temperatures.